Evaluasi Tingkat Usability Learning Management System LiVE Unpad dan Google Classroom Menggunakan Metode System Usability Scale (SUS) - Agung Setiawan; Muhammad Rifqi Arviansyah (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
Universitas Padjadjaran operates an official Learning Management System (LMS) called LiVE Unpad to support digital learning activities. However, usage data and pre-survey results indicate a strong student preference for the external platform, Google Classroom. This study aims to quantitatively measure and compare the usability levels of both platforms using the System Usability Scale (SUS) method. A descriptive-comparative quantitative approach was applied, involving 55 students of Universitas Padjadjaran selected through purposive sampling. The SUS questionnaire instrument was adapted into Bahasa Indonesia and successfully passed validity and reliability testing. The results showed that LiVE Unpad obtained a mean SUS score of 63.86 (Marginal High/OK category), while Google Classroom scored 81.91 (Acceptable/Excellent category). Hypothesis testing using the Wilcoxon Signed-Rank test confirmed a highly significant difference in usability levels between the two platforms (p < 0.001). Primary usability issues identified in LiVE Unpad include a disorganized dashboard layout, an outdated interface design, inadequate notification features, and technical instability.  This study produces interface redesign prototype recommendations for LiVE Unpad as a practical contribution.